1997
DOI: 10.1111/j.1440-0960.1997.tb01700.x
|View full text |Cite
|
Sign up to set email alerts
|

Hidradenitis suppurativa, Dowling Degos disease and perianal squamous cell carcinoma

Abstract: A patient with hidradenitis suppurativa (HS) is described in association with Dowling Degos disease and perianal squamous cell carcinomas. As the initial treatment for HS failed to give any satisfactory relief he sought no further medical help for the subsequent 40 years. This patient illustrates the management difficulties in HS and the need for regular surveillance to exclude the development of anogenital squamous cell carcinoma. Previous reports of hidradenitis suppurativa in association with Dowling Degos … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0
3

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(36 citation statements)
references
References 8 publications
1
32
0
3
Order By: Relevance
“…There have been numerous reports that have associated HS with SCCs of the skin. 24,86,101, The ratio of SCC in HS favors males (4:1). 128 Sixty-one percent of cases were located in the perineum or buttocks; there were no reports of SCC in axillary HS.…”
Section: Disease Associations Key Pointmentioning
confidence: 98%
“…There have been numerous reports that have associated HS with SCCs of the skin. 24,86,101, The ratio of SCC in HS favors males (4:1). 128 Sixty-one percent of cases were located in the perineum or buttocks; there were no reports of SCC in axillary HS.…”
Section: Disease Associations Key Pointmentioning
confidence: 98%
“…This complication is uncommon: since 1958 only 52 cases have been published, most often as case reports – 27 cases were reported in a review in 1995 [15], which omitted 3 additional ones reported up to that time period [16,17,18], 22 additional cases were then published from 1995 to 2008 [19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36]. Lapins et al [37] reported 5 cases of ‘nonmelanoma skin cancer’ among a cohort that may contain some patients who did not have criteria for HS so we did not include those results.…”
Section: Discussionmentioning
confidence: 99%
“…In 1996, a case-control study did not support the association between chlamydial infections and perineal HS [46]. Ten years ago, Li et al [22] were the first to hypothesize that HPV ‘may be an important contributory factor’ to SCC arising in HS, but no histological analysis was undertaken. In 1 case in the literature [26], histological evidence of HPV (koilocytotic atypia) was observed in a biopsy of SCC arising in an anal margin HS.…”
Section: Discussionmentioning
confidence: 99%
“…6 An important association is with HS, as found in our patient, though few cases have been reported in the literature. 1,2,5,7---9 HS is a multifactorial disease that most commonly affects young people Histopathology of a lesion biopsied from the perianal skin: basal hyperpigmentation, digitiform rete ridges, antler-like suprapapillary thinning, dermal melanophages, and a mild perivascular lymphohistiocytic infiltrate (hematoxylin and eosin, original magnification × 10).…”
Section: Enfermedad De Dowling-degos: Caso Clínico Asociado a Hidradementioning
confidence: 77%